SignalP 6.0 predicts all five types of signal peptides using protein language models - Teufel, Felix; Almagro Armenteros, José Juan; Johansen, Alexander Rosenberg; Gíslason, Magnús Halldór; Pihl, Silas Irby; Tsirigos, Konstantinos D.; Winther, Ole; Brunak, Søren; von Heijne, Gunnar; Nielsen, Henrik (Nature biotechnology, 2022)
Signal peptides (SPs) are short amino acid sequences that control protein secretion and translocation in all living organisms. SPs can be predicted from sequence data, but existing algorithms are unable to detect all known types of SPs. We introduce SignalP 6.0, a machine learning model that detects all five SP types and is applicable to metagenomic data. A new version of SignalP predicts all types of signal peptides.